2010
DOI: 10.1007/s10238-010-0120-7
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte subpopulation and dendritic cell phenotyping during antineoplastic therapy in human solid tumors

Abstract: Patients with cancer show variable levels of immunosuppression at the time of the presentation, and cytotoxic antineoplastic therapy is the primary contributor to the clinical immunodeficiency often observed during the course of the disease. In both hematological and solid tumors, this phenomenon is primarily related to the T-cell depletion associated with inhibition of dendritic cell ability to induce both primary and secondary T- and B-cell responses. Complete restoration of immunocompetence following antine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…Studies conducted in recent years have revealed a previously unrecognized complexity of the number and functional status of different immune system subpopulations 35 , 36 . For instance, circulating blood lymphocytes include phenotypically and functionally different cells, such as CD8+ cytotoxic lymphocytes, regulatory T cells and exhausted lymphocytes, whose balance can determine the predominantly antitumor or protumor activity of adaptive immunity 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in recent years have revealed a previously unrecognized complexity of the number and functional status of different immune system subpopulations 35 , 36 . For instance, circulating blood lymphocytes include phenotypically and functionally different cells, such as CD8+ cytotoxic lymphocytes, regulatory T cells and exhausted lymphocytes, whose balance can determine the predominantly antitumor or protumor activity of adaptive immunity 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The potential reason might be that the majority of the patients included in this meta-analysis subgroup were treated with chemotherapy. Compared with the other subsets of T lymphocytes, the CD8 + T cells are more sensitive to cytotoxic chemotherapy and no less than 3 months are required after chemotherapy is terminated to return to baseline cell numbers regardless of the patient's age [ 47 ]. Kondo et al [ 17 ] confirmed this finding in the same subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Although immune cells present in blood might not be restricted to some of the components of the TME, its presence might indirectly reflect the regulators present in TME. Indeed, some studies have correlated different inflammatory biomarkers, such as T cells, DC or NK cells, in blood and tumor tissue samples and found a good correlation between both sites [59,60].…”
Section: Peripheral Bloodmentioning
confidence: 99%